Group dynamics in ESL collaborative academic writing - Yong, Mei Fung (Universiti Putra Malaysia Press, 2014)
Collaborative writing involves group members engaging directly with one another to complete a task. The quality of learning from members is closely associated with the nature of the collaboration and the interactions that take place. This paper examines the dynamics of three groups of tertiary ESL learners as they collaborated on three expository essays. Data were collected from nine audio-recordings of group discussions and four semi-structured interviews. The three cases unveiled very different dynamics due to group connection, individual traits, level of engagement, and degree of control. Social, affective and cognitive processes affected the direction and the quality of collaboration. With an understanding of the group dynamics that ensues during collaboration, practitioners will be better prepared when incorporating collaboration in their writing class.